2011
DOI: 10.1017/s0025315411001408
|View full text |Cite
|
Sign up to set email alerts
|

Association between luminous bacteria and Hydrozoa in the northern Ionian Sea

Abstract: Several hydroid species live associated with many organisms, including bacteria. Hydroid–bacteria associations were searched for in twenty Hydrozoa species that were collected in the northern Ionian Sea and observed under blue light excitation. Of these, six showed high fluorescence on the outer perisarc, five appeared medium fluorescent, four were slightly fluorescent, and five did not show any fluorescence. Luminous bacteria were isolated and counted from the surface of the fluorescent hydroids. Their associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…The hydroid E. crocea represents a mosaic of microenvironments that can be colonized by several organisms, both eukaryotic and prokaryotic, that generally settle only on those portions covered by the exoskeleton [6] [11] , [25] . Several hydroid species have been shown to live with an associated microbial flora [26] , but this is the first study dealing with the presence of bacteria on the hydroid's epidermis documented with a molecular approach combined with electron microscopy. Our molecular analyses revealed that most of the observed prokaryotic diversity was within the domain of Bacteria, whereas Archaea accounted for a negligible fraction.…”
Section: Discussionmentioning
confidence: 99%
“…The hydroid E. crocea represents a mosaic of microenvironments that can be colonized by several organisms, both eukaryotic and prokaryotic, that generally settle only on those portions covered by the exoskeleton [6] [11] , [25] . Several hydroid species have been shown to live with an associated microbial flora [26] , but this is the first study dealing with the presence of bacteria on the hydroid's epidermis documented with a molecular approach combined with electron microscopy. Our molecular analyses revealed that most of the observed prokaryotic diversity was within the domain of Bacteria, whereas Archaea accounted for a negligible fraction.…”
Section: Discussionmentioning
confidence: 99%
“…Since the first identification of Porpita from Indian Ocean (Linnaeus, 1758), its occurrence was continuously reported from various localities in the Indo-Pacific Oceans [4,13,16,20,[26][27][28][29][30][31], Atlantic Ocean and the Mediterranean Sea [15,17,18,[32][33][34][35][36][37][38]. Globally, there are 64 documented occurrences for Porpita (Global Biodiversity Information Facility, GBIF).…”
Section: Figure2 Porpita Porpita From the Red Sea Of Hurghada Coast C...mentioning
confidence: 99%
“…Porpita is known to produce toxic substances which cause skin irritation [10,11] and also contain bioactive compounds having antimicrobial effect [12]. Although P. porpita is native to tropical and sub-tropical waters of the Pacific, Indian and Atlantic oceans and Mediterranean Sea [1,[13][14][15][16][17][18][19][20], its occurrence has not been reported from Red Sea. In general, the interest in documenting diversity of gelatinous zooplankton has not yet received proper attention in the Red Sea, and therefore, little is known about these important aquatic life forms.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, green fluorescent protein (GFP) was first isolated from the jellyfish Aequorea victoria (Shimomura 2005). Since then, fluorescence from a variety of sources has been documented in other hydrozoan taxa (Pugh and Haddock 2010, Gravili et al 2012, Maggioni et al 2020. Despite the history of fluorescence research in hydrozoans, it has yet to be systematically studied within the broad diversity of this animal group, and surprisingly little is known about the distribution and morphological variation of fluorescence in hydrozoans beyond selected genera or species.…”
Section: Introductionmentioning
confidence: 99%